Kesejahteraan Prajurit dan Keluarga Prajurit dalam Operasi Seroja, 1975-1978 - Frido Paulus Simbolon (Medan Resource Center, 2021)
The Seroja military operation involved all ABRI components consisting of the army, navy, air forces and the police. This operation was marked by an attack on the city of Dili by air and sea by the Airborne and Marine troops on December 7, 1975. Soldiers who served in the seroja operation area from 1975 to integration of East Timor with Indonesia were given the title of veteran defense of Seroja, while soldiers who served after East Timor integration, is not classified as a veteran of Seroja's defense. For the Warakawuri Seroja and Penca Seroja, the government builds housing for their residence. In addition to obtaining the right to a place to live, the government also fulfills the welfare of employees and people with other benefits beyond the salary of retirees, as well as rewards, although in fulfilling the welfare and rights of warakawuri and people with disabilities, this does not always work well. The conclusion in this study is that the welfare of soldiers and their families of soldiers who served in the Seroja Operation area received attention from the government and also ABRI as the institution where they served. Operation after operation was carried out until on July 17, 1976 East Timor was officially integrated in Indonesia and became the 27th province of the Republic of Indonesia. In carrying out Seroja's military operations, the government through the ABRI institution certainly pays attention to the welfare of both soldiers and their families. Apart from that, ABRI also paid attention to the welfare of the families of soldiers who died in the field of seroja operations as well as soldiers who were injured while carrying out their duties in the seroja operation area.